University of the future: a new paradigm - Ridwan, Azrina Wahi; Mohamed Yusof, Nurul 'Atiqah; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
The challenges ahead for higher education not just in Malaysia but around the world appears driven by disruptive change in the forces of technology, economic, political and education sector which threaten to undermine its business model, governmental support and operating mission. Thus, the purpose of this paper is to build a successful future business model canvas for university of the future while addressing a number of challenges in the coming years. A total of 20 respondents were interviewed encompassing two customer profiles which are endowment contributors and investors. Based on the analysis, a more comprehensive business model canvas (BMC) and value proposition design (VPD) were established fit the upcoming higher education system’s environment. The number of respondents was rather small due to time limitation. The results are predominantly beneficial to universities, policy makers, business organizations and students by offering a comprehensive understanding into the new practical business model into the future. This study offers a beneficial source of information to each party to produce incredible strategies for higher education sector that meet global needs.